2016
DOI: 10.7448/ias.19.1.21111
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ experience of a rapid HIV self‐testing device in youth‐friendly clinic settings in Cape Town South Africa: a cross‐sectional community based usability study

Abstract: Introduction: Since HIV testing in South African adolescents and young adults is sub-optimal, the objective of the current study was to investigate the feasibility and acceptability of an HIV rapid self-testing device in adolescents and young people at the Desmond Tutu HIV Foundation Youth Centre and Mobile Clinic. Methods: Self-presenting adolescents and young adults were invited to participate in a study investigating the fidelity, usability and acceptability of the AtomoRapid HIV Rapid self-testing device. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
49
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 22 publications
8
49
1
Order By: Relevance
“…A study conducted among 16-24 years olds in South Africa to evaluate self-testing using a rapid blood test demonstrated that 96.4% completed the test correctly and were able to interpret the test results (48), and only 3% of participants failed to prick their finger (48). In recent years, HIV self-testing using oral mucosal transudate (OMT) HIV tests has been shown to be highly acceptable and accurately performed by adults in SSA (37,49).…”
Section: Hiv Testing and Counselling Strategies For Adolescentsmentioning
confidence: 99%
“…A study conducted among 16-24 years olds in South Africa to evaluate self-testing using a rapid blood test demonstrated that 96.4% completed the test correctly and were able to interpret the test results (48), and only 3% of participants failed to prick their finger (48). In recent years, HIV self-testing using oral mucosal transudate (OMT) HIV tests has been shown to be highly acceptable and accurately performed by adults in SSA (37,49).…”
Section: Hiv Testing and Counselling Strategies For Adolescentsmentioning
confidence: 99%
“…Video evaluation showed multiple errors in specimen collection, use of buffer, read times and interpretation of results, regardless of whether the kit was oral fluid based or blood based [16]. Errors persisted even after self-test prototypes were further adapted [9,10,12,14,17]. Blood-based self-tests have been shown to be more sensitive than oral fluid-based tests, but evidence suggests that invalid results among self-testers may be also be higher [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Young people's preferences for blood based HIVST was surprising given the high preference for facility-based HIV testing. This discordance in preference for HIV testing could be because of limited [16,23], Asia [24] and Europe [25]. Our findings also suggest that in addition to increasing knowledge of and awareness of HIV prevention, efforts should be made to integrate information on the full range of testing approaches and prevention tools currently available within Nigeria [2].…”
Section: Discussionmentioning
confidence: 99%